Ketaatan Elia Kepada Allah (Eksegesis 1 Raja-Raja 17:1-6) Dan Relevansinya Bagi Orang Percaya Masa Kini - Erickson Nanda Putra Halawa; Hetri Anida Siregar; Herdiana Br. Hombing (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
Elijah's obedience is evident in his faithfulness to listen and obey God's commands. Through an understanding of the Biblical text, Elijah's obedience to God is analyzed in the context of perseverance, compliance, and complete trust in God's plan. This study also explores the relevance of Elijah's obedience for present-day believers. In a world filled with challenges and uncertainties, the lessons from Elijah's story provide inspiration about the importance of faith, obedience, and reliance on God. It offers a perspective that enriches how believers can lead their everyday lives with deep obedience to God's will, gaining strength and courage from their faith. This research reveals that Elijah's obedience reflects strong relevance for present-day believers, emphasizing the importance of strengthening the spiritual connection with God, following His will, and believing that obedience to Him brings blessings and protection. The practical implications of Elijah's obedience can encourage believers to deepen their faith, enhance their obedience, and broaden their perception of God's power and presence in everyday life.